(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
The demands on companies, especially on their ability to innovate, have risen dramatically in recent years. Hence, the importance of partnerships, networks, clusters and ecosystems has increased. When aiming for innovation it is generally accepted that merging various skills may lead to competitive advantages. So-called innovation ecosystems would like to promote and accelerate this. In general, ecosystems are understood as a space in which various actors are located. Each actor behaves according to certain roles. Each role is associated with specific tasks. Little is known about the actors, roles and tasks within an innovation ecosystem. The objective of this paper was to illustrate these three aspects in one model. From various scientific theories, a model has been developed that can be used to describe innovation ecosystems. The developed model has been applied to a real innovation ecosystem, the Lake Constance region in Germany, and has been validated by a qualitative survey in the form of expert interviews. The key results are that innovation ecosystems can be visualized with the developed model and that the interviewed experts could identify themselves with the given roles and tasks. Moreover, additions to the model were proposed during the expert interviews. Based on that research, a new understanding of regional clusters is introduced with the aim of developing clusters into instruments for promoting innovation. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.